Approach to the management vision of rural area from the perspective of decent work. case study: rural managers from Araure, Portuguesa state (Dissertare, 2016)
The work is an activity which man develops, through he can satisfy needs and crystallize his dreams. People who perform management functions motorizing workers, should act in response to their workers develop in environments of justice, making decisions, ensuring social security, among other features contemplated in Decent Work, (DW). This study aims to collect the interpretation from the perspective of managers in rural areas with respect to DW. Assuming the principle of Administration and social science  based on the methodological possibilities which let the interpretative paradigm, I try to develop the meaning that managers of rural areas have given to Decent Work; channeled in an ethnographic design, which aims to describe, analyze and interpret, among others things, the meaning of what people do, with emphasis on daily activities. As a data collection technique, I used depth interviews, which allow me to contact managers in rural areas face to face, to listen to their perceptions and their applicability about the topic in this area. Then, I proceeded to describe, analyze and interpret these perceptions. Regarding techniques of analysis and interpretation of findings, I relied on those provided by the hermeneutical method. Among the findings, there was the satisfaction of knowing how rural managers are concerned about their workers, checking that decent work materializes in Portugueseño field. There is a heartfelt social conscience in rural managers which was manifested in their interaction with workers.
Keywords: management vision; rural managers; decent work; rural management.